2022
DOI: 10.2172/1839593
|View full text |Cite
|
Sign up to set email alerts
|

SolarAPP+ Pilot Analysis: Performance and Impact of Instant, Online Solar Permitting

Abstract: This report is available at no cost from the National Renewable Energy Laboratory (NREL) at www.nrel.gov/publications. U.S. Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…This report provides a more comprehensive picture of the overall performance of SolarAPP+ beyond the pilot jurisdictions, including additional insights regarding the slate of projects approved through the platform in participating jurisdictions in 2021. As we shall discuss, our more comprehensive study largely affirms previous results from Williams et al (2022).…”
Section: Figure 2 Example Solarapp+ Permit Application and Approval P...supporting
confidence: 89%
See 4 more Smart Citations
“…This report provides a more comprehensive picture of the overall performance of SolarAPP+ beyond the pilot jurisdictions, including additional insights regarding the slate of projects approved through the platform in participating jurisdictions in 2021. As we shall discuss, our more comprehensive study largely affirms previous results from Williams et al (2022).…”
Section: Figure 2 Example Solarapp+ Permit Application and Approval P...supporting
confidence: 89%
“…Across all AHJs in 2021, median project times were 13 days shorter for SolarAPP+ projects than for traditional projects (32 days compared to 45 days). This estimate is similar to results from Williams et al (2022), who found that projects were installed 12 business days faster than those installed via the traditional process for the five pilot AHJs. The difference in the median project time between SolarAPP+ and the traditional process is an approximation of the cumulative impact of SolarAPP+ and does not control for potential differences between applications submitted through each process.…”
Section: Solar Adoption Timeline Impactssupporting
confidence: 87%
See 3 more Smart Citations